Evaluating the Effectiveness of Cyclin-Dependent Kinase 4/6 Inhibitors in Early- and Very Early-Onset Metastatic Breast Cancer: A Multicenter Study - Akif Doğan; Nurullah İlhan; Goncagül Akdağ; Sedat Yıldırım; Mustafa Seyyar; Zeynep Yüksel Yaşar; Hande Nur Erölmez; Heves Sürmeli; Buğra Öztosun; Özlem Nuray Sever; Hatice Odabaş; Mahmut Emre Yıldırım; et al. (Medicina)
Background and Objectives: Early-onset breast cancer (EOBC), particularly in patients under 40, presents with distinct biological characteristics and worse survival outcomes compared to late-onset cases. Despite intensive treatments, EOBC patients, especially those with hormone receptor-positive, HER2-negative (HR+/HER2-) subtypes, show poorer prognosis. CDK4/6 inhibitors, combined with endocrine therapy (ET) have become the standard for HR+/HER2- metastatic breast cancer, yet younger patients are underrepresented in clinical trials. This study aims to evaluate the efficacy of ribociclib and palbociclib with ET in HR+/HER2- metastatic breast cancer, addressing the critical gap in understanding treatment outcomes in younger patient populations. Materials and Methods: This multicenter, retrospective study evaluated the efficacy and safety of cyclin-dependent kinase 4 and 6 (CDK 4/6) inhibitors, ribociclib, and palbociclib, in combination with endocrine therapy in patients with hormone receptor-positive and human epidermal growth factor receptor 2-negative metastatic breast cancer. Results: A total of 198 patients treated between 2019 and 2023 were analyzed for progression-free survival, overall survival, and prognostic factors. Very early-onset breast cancer, which is diagnosed before the age of 35, was identified as an independent prognostic factor for poor progression-free survival. Additional factors associated with poorer outcomes included liver metastasis, progesterone receptor negativity, high tumor grade, and the concurrent use of fulvestrant with CDK4/6 inhibitors. Both ribociclib and palbociclib demonstrated similar efficacy, and dose reductions due to treatment-related adverse events did not compromise therapeutic outcomes. Conclusions: This study is the first to focus specifically on the treatment of early-onset breast cancer with CDK4/6 inhibitors, providing critical insights into the unique challenges faced by this patient population. The findings underscore the urgent need for personalized treatment strategies, routine genetic testing, and dedicated clinical trials designed to address the specific needs of these high-risk subgroups. By advancing our understanding of the clinical and molecular landscape of early-onset breast cancer and very early-onset breast cancer, this study lays the groundwork for improving outcomes in these underserved patients through tailored therapeutic approaches.